Ethical Work Climate Untuk Menciptakan Moral Awareness Karyawan Pada Koperasi Bank Perkreditan Rakyat Tribakti Nganjuk - Siti Sulasmi; IGM Dwi Widhianto (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2009)
This study would examined empirically which one of these ethical criteria, namely self-interest, company, interest, efficiency, friendship, team play, social responsibility, personal morality, rules and procedures, and the law or professional code variables as the criteria’s to create Ethical Work Climate influenced significantly upon moral awareness of the 170 marketing division employee of TRIBAKTI KBPR (Koperasi Bank Perkreditan Rakyat – People Credit Cooperative Bank) in Nganjuk East Java. The result showed that self-interest, company interest, efficiency, friendship, team play, social responsibility, personal morality, rules and procedures, as well as professional code variables simultaneously create significantly employees moral awareness. Individually, rules and procedure, friendship, team play, personal morality, as well as the law or professional code variables were the ethical criteria that significantly arouse moral awareness. While self-interest criteria variable was to some extent significant, it were contrary to moral awareness development of KBPR’s employees. The other three Ethical Work Climate variables, namely company interest, efficiency and social responsibility showed no significant effect.